Regulating social entrepreneurship in Russia - N. I. Zvereva; N. Yu. Surova (Вестник Российского экономического университета имени Г. В. Плеханова)
In Russia social enterprises (entities of social entrepreneurship) are set up and develop during the last decade. In 2012 they were included in the state program of support for small and medium entrepreneurship. The growth in the number of social entrepreneurship and the experience of state regulation and support to their work accumulated within the period 2012 – 2017 stipulate the need to systematize and analyze this managerial experience. The article describes the origin of the system of state regulation in the field of social entrepreneurship in Russia. It shows that today the process of establishment and development of the conceptual kit, goals, tasks and tools of state policy is going on. Having studied tools of legislative regulation, infrastructure, education and finance support to entities of social entrepreneurship in Russia the authors pointed to the absence of the unique program of this sector development, which is obvious in dividing all tools of support in accordance with organizational-legal forms of social enterprises and it actually duplicates infrastructure and makes administration of finance support more difficult. The authors put forward recommendations dealing with designing a unique program of social entrepreneurship development in Russia with adopting relevant legislation and correcting the mechanism of managing this sector of economy on the part of state.